Pembuatan Sistem Peramalan Penjualan Dengan Metode Weighted Moving Average dan Double Exponential Smoothing Pada UD Y - Cindy Baktiar; Adi Wibowo; Rudy Adipranata (Jurnal Infra, 2015)
UD Y is a small business, that provides distribution of water pumps and the spareparts (capacitor, seal, fan) as well as manufacturing the accessories (valves, pvc tees and tanks). UD Y as a commercial industry, finds it hard to forecast the right amount of materials needed to produce their products. For that reason, for this thesis will be made a Sales Forecasting using the Weighted Moving Average and Double Exponential Smoothing methods to help UD Y to forecast the right amount of products that will be bought every month.This system was made using database MySQL with Hypertext Prepocessor (PHP) programming languageFrom the final testing of this program, system that has been made can show the sales forecast in UD Y so that system can help UD Y from making decision for the right amount of products stock.